The 15-Minute City Model: The Case of Sicily during and after COVID-19 - Socrates Basbas; Tiziana Campisi; Thomas Papas; Mirto Trouva; Giovanni Tesoriere (Communications, 2023)
Travel restrictions due to COVID-19 initiated a radical rethink of the urban planning process, focussing on a concept initially proposed by Carlos Moreno in 2016; the "15-Minute City" model, aiming at the improvement of quality of life by creating or rearranging cities so that residents' needs can be reached within 15-minutes on foot or by bicycle or by public transit. In continuation to a research in 2020, this paper quantifies the attractiveness of the model to residents in nine regions of Sicily in 2022. Based on statistical analysis concerning the respondents' opinion, the model examined promotes walking as an anti-stress method and improves the overall health conditions at a community level. Therefore, policy makers can revalue the existing planning process and create a blueprint for a healthier and car-free lifestyle.